A critique of various pastoral care methods in regard to the traumatic death of a child : the traumatic death of a child - a challenge for pastoral care - Masango, Maake J.S (University of Pretoria, 2013)
Dissertation (MA (Theology) : Practical Theology)--University of Pretoria, 2008.